2020
DOI: 10.1002/eat.23290
|View full text |Cite
|
Sign up to set email alerts
|

Support for a two‐dimensional model of food craving using self‐report questionnaire and cue‐reactivity methodologies

Abstract: Objective Evidence supports the transdiagnostic importance of food cravings across the spectrum of disordered eating behaviors. The ambivalence model of craving (AMC), originally applied to substance use craving, highlights the need to consider not just the motivational state of “approach,” but also that of “avoidance.” The aims of this project were to (a) extend the existing literature by providing additional psychometric support for the food approach and avoidance questionnaire (FAAQ), (b) extend research su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Second, this study utilized self-reported BMI. Though this has drawn criticism by some, data suggest a strong correlation between self-reported BMI and measured BMI (e.g., Ahlich et al, 2020; McAdams et al, 2007). In addition, the present study did not include a clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study utilized self-reported BMI. Though this has drawn criticism by some, data suggest a strong correlation between self-reported BMI and measured BMI (e.g., Ahlich et al, 2020; McAdams et al, 2007). In addition, the present study did not include a clinical sample.…”
Section: Discussionmentioning
confidence: 99%